PENGARUH TOTAL ASSETS TURNOVER (TATO), RETURN ON ASSETS (ROA), EARNING PER SHARE (EPS) DAN PRICE EARNING RATIO (PER) TERHADAP HARGA SAHAM - Putri Jayantiningtyas Sudiro, 12.05.51.0039; ., Sri Sudarsi (Students Journal of Economic and Management, 2016)
The purpose of this study was to examine the influence of Total Assets Turnover, Return on Assets, Earning Per Share and Price Earning Ratio of share price on publicly traded companies incorporated in LQ45 Index in 2012-2014. This research was conducted using secondary data. The population in this study are all publicly traded companies incorporated in LQ45 Index in 2012-2014. The sample in this study using purposive sampling method. The analytical method used in this research is multiple regression analysis. The research proves that, EPS and PER positive and significant impact on stock prices, ROA significant negative effect on stock prices and TATO and not significant positive effect on stock prices. Adjusted R Square value is 0,999 this means that 99.9% of the dependent variable can be explained by the independent variable, while the remaining 0.1% is explained by other causes outside the model. Keywords: Share Prices, Total Asset Turnover, Return on Assets, Earning Per Share and Price Earning Ratio.